Development of an automated reading tutor in Filipino for primary students - Pascual, Ronald M.
The current problems that the country's education system are facing, such as the poor reading performance of the students and the shortage of teachers, inspired us to focus on the development of a computer software program for an Automated Reading Tutor (ART) in Filipino, an alternative learning system based on Oral Reading Fluency (ORF) instruction and Automated Speech Recognition (ASR) technology. The focus of Filipino language is mainly motivated by the Mother Tongue-Based Multilingual Education (MTBMLE) drive by the Department of Education. A Children's Filipino Speech Corpus (CFSC) was collected for the purpose of creating the speech models and the offline test set. The CFSC contains a total of about 8 hours of continuous speech of 57 Grades 1-5 students, which were recorded while the students read various age-appropriate Filipino short stories. The CFSC contains both "good" pronunciations and examples of reading miscues/disfluencies. We propose a design for the Reading Miscue Detector (RMD) that is based on a two-level Reference Verification (RV) and Word Duration Analysis (WDA) methods. The speech HMMs were built by training the system with 1.5 hours of phone-level transcribed speech from the CFSC. We perform offline tests that evaluate the performance of the system in terms of False Alarm (FA) and Miscue Detection Error (MDerr rate of 5%) that is at par with state-of-the-art ART systems for English. we present the design of the ART prototype that integrates the proposed RMD, the user interface, and the Feedback and Instruction sets. In order to evaluate the effectiveness of the ART, we conducted an ART Intervention program, a month-long pilot study that involved the use of the ART by a small group of students. Results show that the students are able to achieve a significantly higher improvement in their reading fluency after using the ART. On the average, the students' Words Correct Per Minute (WCPM) rates, ORF-16 scores and comprehension scores have improved by 4.66, 6.0, and 4.33 times respectively, after using the ART. On a 4-point scoring scale, with 4 being the highest, the proposed ART system received an overall evaluation of 3.5 from teachers and parents. Other important observations derived from the experiences with the implementation of the ART Intervention program are also presented.